Understanding the preference of online health information seeking among college students using the best-worst scaling method - Wang, Dan; Jiang, Wang; Chen, Haihong; Chen, Manli; Gong, Guangwen; Sun, Yansun; Wu, Yajing; Wang, Xuemei; Li, Xiping (Frontiers in Public Health, 2025)
BackgroundWith the overwhelming availability of online health information and high prevalence of health misinformation, it is vital to understand the status and key influencing factors of its use among individuals. This study aims to explore the online health information-seeking behavior and preference of the influencing factors among college students.MethodsWe used the best-worst scaling approach to determine college students’ preferences for factors influencing online health information-seeking behavior. A total of 11 attributes of online health information seeking were confirmed by literature review and focus group, and a balanced incomplete block design was used to create 11 tasks for the BWS survey. An online survey was conducted from March 2023 to May 2023 using the BWS survey questionnaire.ResultsBoth the BWS score and mixed logit model results indicate that “verified by professional institutions or health professionals”(mean BW=1.938; coefficient = 3.096), “information source from trustworthy and authoritative website”(mean BW = 1.921; coefficient = 3.015), “privacy and security guaranteed”(mean BW = 1.234; coefficient = 2.637), and “consistency of information” (mean BW = 0.803; coefficient = 2.313) were the most important factors and were valued more positively than negatively by respondents. The results showed the covariate of medical education had positive effects of 0.410 and 0.279 on the preference of “writing and language” and “professional interface design,” while medical education background had negative effects of −0.307 on the preference of “disclosure of author information.”ConclusionWe recommend that concerned authorities consider interventions targeting the accuracy, credibility, privacy, and consistency of online health information management for college students.